Cultural Persons’ Representations in High School English Language Teaching Materials in Indonesia - Putri, Sefhia Kurnia; Suharni, Suharni; Autia, Rani (Jurnal Akuntansi Hukum dan Edukasi, 2024)
Integrating both local and target cultures in English Language Teaching Materials and emphasizes the need for balance to promote cultural diversity and understanding become an important thing in today’s era. During teaching practice activities at SMAN 17 Tebo, the researcher found that the cultural materials in the English Teaching Materials used are not balanced between the source culture, target culture, and international culture. This has an impact on cross-cultural understanding and less than optimal cultural awareness among students. The purpose of this research is to explore the representation of cultural persons in government textbook and teacher-made modules. This research uses qualitative content analysis as a research design. This research involved a sample of government-approved English language textbooks entitled “Bahasa Inggris Work in Progress” and a teacher-made module at SMAN 11 Tebo. The results show that from the theme of great athletes in chapter one of the Bahasa Inggris Work In Progress textbook and teacher-made module, it can be seen that the dominant sports branch comes from international culture. While the cultural persons represented as athletes are dominated by the source culture. It is recommended that future development of English language teaching (ELT) materials, both in government textbooks like Bahasa Inggris Work in Progress and teacher-made modules, should strive for a more balanced representation of source culture, target culture, and international culture for fostering intercultural competence among Indonesian students.